Task-Specific Organic Salts and Ionic Liquids Binary Mixtures: A Combination to Obtain 5-Hydroxymethylfurfural From Carbohydrates - Marullo, Salvatore; Rizzo, Carla; D'Anna, Francesca (Frontiers in Chemistry, 2019)
The increase in energy demand and depletion of fossil fuels are among major issues of modern society. Valorization and transformation of raw materials in products of industrial value represents a challenge. This justifies the growing interest of scientific research towards the identification of suitable media and methodologies able to pursue above goals, paying attention to matter of sustainability. On this subject, we studied sulfonic-acid functionalized diimidazolium salts as catalysts for the conversion of fructose and sucrose to 5-hydroxymethylfurfural (5-HMF) in an ionic liquid mixture. In general, using these salts allowed us to obtain 5-HMF in good yields from both substrates in mild conditions. Indeed, at 60 °C and in the presence of 20 mol % of catalyst, 5-HMF yields of 60 and 30 % were obtained from fructose and sucrose, respectively. The catalytic system was recycled and used up to six times observing no appreciable loss in yield for the first four cycles. Moreover, we gathered mechanistic information by in situ 1H NMR monitoring the dehydration of fructose. To dissect the role of acidity on the reaction, we determined the Hammett acidity function of each salt. Comparison of these results with yields and reactivity observed in the presence of related monocationic salts and with a dicationic salt bearing only one sulfonic acid group allowed stating that the reactivity observed is the result of the combined action of acidity and structural features of the catalysts. Overall, the approach proposed here could contribute to pave the way to increase sustainability in the raw material valorization processes.